Impact of public passenger transport organization model on system performance and service quality - Pitka, Pavle; Simeunović, Milan; Milenković, Ivana; Simeunović, Milja; Škiljaica, Ivan (Transport, 2023)
Organization and management of Public Passenger Transport (PPT) system is a complex process, which significantly impacts the functioning of the system. Globally, there is no unique solution for organization model of PPT, but the organization models are adjusted to the characteristics of each individual area. Organization model of PPT, inherited from the self-management system of the former Socialist Federal Republic (SFR) Yugoslavia, became unsustainable in the Municipality of Inđija (Serbia) and did not fulfil transport needs and demands of passengers regarding the amount of transport and its quality in optimal manner. Old organization model has been replaced by a new modern model, based on positive experiences from developed European cities. Article presents the impact of new organization model of PPT on the work of the system. Research has been conducted in order to determine the state of both old and new system’s organization model by counting and interviewing passengers during years 2008 and 2017. In accordance with the changes made in the system, comparative analysis “before and after changes” has been done along with establishing of the effects of changes on functioning of the system and service quality. Results show significantly improved service quality, while transport demands increase by 38.3%.